MIKROPROPAGASI ANGGREK ALMA Grammatophyllum scriptum Blume - Handini, Elizabeth (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2008)
Grammatophyllum scriptum is a beautiful wild orchid that has an interesting economic value. However, the existence of this ornamental plant species is at risk because of irresponsible exploitation of the natural population and insufficient cultivation efforts. Currently, the Bogor Botanic Garden is developing a program of orchid propagation for enhancing the conservation of all potential orchid collections. The propagation of G. scriptum was basically carried out by culturing the seeds in a modified Hyponex or Vacin & Went medium, transplanting the plantlets into a more suitable medium and finally acclimatizing the resulting seedlings. A study was done to observe the effect of fertilizer application on the growth of acclimatized G. scriptum seedlings, as a means to improve the propagation technique of the species. The result showed that the application of 1 and 2 m1/I organic fertilizer (Sugih) as well as 1 and 2 g/I inorganic fertilizer (Hyponex) increased the seedling mortality, in which the application of 2 g/ml Hyponex fertilizer was being the most damaging treatment, leaving 12,5 % seedlings to survive. However, in terms of seedling growth, the application of 1 m1/I Sugih fertilizer was slightly beneficial to the formation of root and the elongation of stem of the acclimatized seedlings. It may be suggested, therefore, that G. scriptum seedlings require no (or very little amount of) supplementary fertilizer to boost their vegetative growth.